Institutions and contract enforcement - Armin Falk; David Huffman; W. Bentley MacLeod (Center for Economic Studies and ifo Institute (CESifo), 2008)
We provide evidence on how two important types of institutions - dismissal barriers, and bonus pay - affect contract enforcement behavior in a market with incomplete contracts and repeated interactions. Dismissal barriers are shown to have a strong negative impact on worker performance, and market efficiency, by interfering with firms' use of firing threat as an incentive device. Dismissal barriers also distort the dynamics of worker effort levels over time, cause firms to rely more on the spot market for labor, and create a distribution of relationship lengths in the market that is more extreme, with more very short and more very long relationships. The introduction of a bonus pay option dramatically changes the market outcome. Firms are observed to substitute bonus pay for threat of firing as an incentive device, almost entirely offsetting the negative incentive and efficiency effects of dismissal barriers. Nevertheless, contract enforcement behavior remains fundamentally changed, because the option to pay bonuses causes firms to rely less on long-term relationships. Our results show that market outcomes are the result of a complex interplay between contract enforcement policies and the institutions in which they are embedded.
Keywords: J41; J3; C9; D01; 330; institutions; contracts; contract enforcement; market experiment; Arbeitsvertrag; Leistungsmotivation; Kündigungsschutz; Leistungsorientierte Vergütung; Test